2004
DOI: 10.1021/cm048810n
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Reduction of NiO Using Reactive Ball Milling under Hydrogen Atmosphere Leading to Ni−NiO Nanocomposites

Abstract: Controlled mechanochemical reduction of NiO has been carried out by room-temperature ball milling under H 2 atmosphere. During the milling, a gradual conversion of NiO into Ni occurs, with no intermediate phases being formed. The amount of Ni and its crystallite size can be tuned by the ball-milling parameters, leading to the formation of Ni-NiO (metaloxide) nanocomposites. The initial microstructure of the NiO powder is shown to play an important role in the reduction rate and on the final microstructure of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 30 publications
0
24
0
1
Order By: Relevance
“…The reduction process was carried out for 5 h. The reduction reaction took place at the interface between the oxide and the reduced Ni. Hydrogen reduces NiO to Ni as per the following reaction (Doppiu et al, 2004).…”
Section: Experimental Set-upmentioning
confidence: 99%
“…The reduction process was carried out for 5 h. The reduction reaction took place at the interface between the oxide and the reduced Ni. Hydrogen reduces NiO to Ni as per the following reaction (Doppiu et al, 2004).…”
Section: Experimental Set-upmentioning
confidence: 99%
“…Nanoparticles in core-shell morphology are of interest in their own right and have been the subject of extensive research in the recent past [1,4,5]. The passivating oxide layer on ferromagnetic metal plays a significant role in modifying the global magnetic properties of nanostructures.…”
Section: Introductionmentioning
confidence: 99%
“…For example, NiO layer formed around Ni can result in an antiferromagnetic (AFM)-ferromagnetic (FM) interaction, thereby reducing net magnetization. Besides, coupling of FM particles with AFM matrix can be a source of a large effective anisotropy, which leads to a marked improvement in the thermal stability of the moments of FM NPs [4,5]. Influence of surface and interface anisotropy has also been invoked as the origin of anomalous magnetic properties of NPs at low temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…Doppiu et al [82] demonstrated that Ni can be formed controllably by partial reduction of NiO upon reactive ball milling, leading to Ni-NiO nanocomposites. Mechanochemical reduction of NiO was carried out at room temperature by ball milling under H 2 atmosphere.…”
Section: Ni-based Nanomaterials and Nano Compositesmentioning
confidence: 99%